2020
DOI: 10.1038/s41436-019-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel ZRS variant causes preaxial polydactyly type I by increased sonic hedgehog expression in the developing limb bud

Abstract: Purpose: Preaxial polydactyly (PPD) is a common congenital hand malformation classified into four subtypes (PPD I-IV). Variants in the zone of polarizing activity regulatory sequence (ZRS) within intron 5 of the LMBR1 gene are linked to most PPD types. However, the genes responsible for PPD I and the underlying mechanisms are unknown. Methods: A rare large four-generation family with isolated PPD I was subjected to genome-wide genotyping and sequence analysis. In vitro and in vivo functional studies were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Shh is expressed at the posterior margin of the limb buds in vertebrates, specifying an anteroposterior pattern in developing limbs by stimulating the proliferation of mesenchyme and regulating the anteroposterior length of the apical ectodermal ridge. As we previously reported, ectopic anterior expression of SHH in the hindlimbs led to preaxial polydactyly in ZRS g.101779T>A homozygous mice models (Xu et al, 2020). Yoshiyuki et al demonstrated that a severe lack of SHH signaling led to the polydactyly, syndactyly, and brachydactyly in homozygote hereditary multiple malformation mutant (hmm −/− ) mouse embryos.…”
Section: Discussionmentioning
confidence: 68%
“…Shh is expressed at the posterior margin of the limb buds in vertebrates, specifying an anteroposterior pattern in developing limbs by stimulating the proliferation of mesenchyme and regulating the anteroposterior length of the apical ectodermal ridge. As we previously reported, ectopic anterior expression of SHH in the hindlimbs led to preaxial polydactyly in ZRS g.101779T>A homozygous mice models (Xu et al, 2020). Yoshiyuki et al demonstrated that a severe lack of SHH signaling led to the polydactyly, syndactyly, and brachydactyly in homozygote hereditary multiple malformation mutant (hmm −/− ) mouse embryos.…”
Section: Discussionmentioning
confidence: 68%
“…PPD I is a frequent developmental defect worldwide, while disease-causing variants have only been identified in a few patients ( Ullah et al, 2019 ; Umair et al, 2019 ; Xu et al, 2020 ). Genetic etiologies of most cases remain to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…PPD occurrence is accompanied by an increase in cell proliferation and migration in the anterior-proximal region of limb buds ( Crick et al, 2003 ). Variants in GLI3 and ZRS cause PPD by inducing the anterior ectopic expression of SHH ( Deng et al, 2015 ; Xu et al, 2020 ). SHH promotes cell proliferation and migration in vivo and in vitro ( Hayes et al, 2001 ; Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2H), suggesting that this partition of the ZPA in distinct sub-regions may correspond to alternative ZRS-associated TFs. This hitherto hidden level of spatial and regulatory diversity in the ZPA therefore may further contribute to the diversity of limb morphologies resulting from ZRS genetic variants [44][45][46] as they may change Shh expression modulate its impact on target genes in either the proximal or distal part of the ZPA [41].…”
Section: Tattoo-seq Characterizes the Spatial Patterning Of The Limb Budmentioning
confidence: 99%